Current Transport in Graphene/Copper Hybrid Nano Ribbon Interconnect: A First Principle Study. (25th August 2016) - Mohsin, K M; Srivastava, Ashok; Sharma, Ashwani K; Mayberry, Clay; Fahad, Md S
Abstract : Recent studies have shown superior thermal transport of graphene on copper as a potential candidate for the next generation interconnects. Using density function theory (DFT) we have studied the current transport of graphene/copper (G/Cu) hybrid-nano wire interconnect system and compared with graphene interconnect. From the first principle calculation, band structure and density of states have been calculated. Using Landauer-Buttiker (LB) formalism, electrical transport is calculated. For this presented G/Cu system, we found resistivity as 1.25x10 -6 Ω-m, which is one tenth of Cu-bulk resistivity. G/Cu hybrid interconnect shows more conductive than graphene only interconnect for low bias applications.